PERANCANGAN USULAN TATA LETAK FASILITAS DI CAFE DAMASCUS - Syahrul Astiono, Ridho; Sugianto, Welly (LPPM Universitas Putera Batam, 2022)
This study aims to be able to provide a proposal for improvement in the layout design of the Damascus cafe, so as to reduce the distance between facilities, as well as design a storage room and kitchen in the cafe. Cafe Damascus is demanded to be able to design an optimal layout and design a layout in order to minimize the distance between facilities as well as to design a storage room and kitchen that has been properly arranged so that it is more effective in terms of the distance between facilities. The data that needs to be taken by looking directly at the cafe area and interviews with cafe owners. In this research, the method used is Activity Relationship Chart (ARC), and BLOCPLAN application. From the results of research that has been carried out the initial layout of the cafe has not been determined because the cafe is still in the layout design stage, therefore research is carried out on a good cafe design from the efficiency of the distance between facilities. The results obtained from the analysis of the proposed layout using the Activity Relationship Chart (ARC) method, and the required distance BLOCPLAN are more optimal because the placement of cafe facilities is more effective with a distance of 25.24 m and an efficiency of 11.7%, the analysis carried out on the production process and the distance between facilities using the Activity Relationship Chart (ARC) and BLOCPLAN methods has reduced the distance between facilities so that the Cafe Damascus coffee production process is more efficient.